Gotong Royong sebagai Modal Sosial dalam Menghadapi Pandemi di Kota Surabaya - Noviyanti Noviyanti; Unggul Sudrajat (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2021)
Surabaya is the city with the highest positive covid-19 confirmation in East Java, Indonesia.Accordingly, Surabaya’s city government have tried to use variety of methods to prevent the spread of the virus. The government expect the Surabaya society’s participation to take an action, working together with them to against it. As the social capital, the tradition of cooperation can be used to deal with the spread of the Covid-19 outbreak. The aim of this research is to analyse the role of Mutual Cooperation (gotong-royong) as social capital in the Surabaya’s communities when they deal with the covid-19 pandemic. This research used qualitative methods. The data collection was carried out through literaturestudy and virtual interview. The result of this research indicates that cooperation between community activities is very useful. Beside being able to help with the items needed for handling Covid-19, Mutual Cooperation can also make coordination and cooperation between society and local government more effective and efficient.